2006
DOI: 10.1089/jir.2006.26.83
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Groups of Smoldering Multiple Myeloma Patients Who Are Either High or Low Producers of Interleukin-1

Abstract: Interleukin-1beta (IL-1beta) is abnormally expressed by the plasma cells obtained from myeloma patients, and it is a potent inducer of the important myeloma growth factor, IL-6. We investigated whether levels of IL-1beta biologic activity might distinguish different groups of patients with smoldering multiple myeloma (SMM). We measured the ability of IL-6 production by bone marrow stromal cells to serve as a surrogate marker for IL-1beta biologic activity. Using this IL-1beta bioassay, we found that it is sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 43 publications
0
49
0
3
Order By: Relevance
“…The effect on IL-6 production was inhibited by IL-1 antagonists. 20 This finding indicates that IL-1b is linked with the progression of MGUS to MM. We found that homozygous carriers of the variant C-allele of IL-1b T-31C were at increased risk of MM (relative risk of 1.37; CI ¼ 1.05-1.80) compared with random samples of healthy Danes aged 50-64 years.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The effect on IL-6 production was inhibited by IL-1 antagonists. 20 This finding indicates that IL-1b is linked with the progression of MGUS to MM. We found that homozygous carriers of the variant C-allele of IL-1b T-31C were at increased risk of MM (relative risk of 1.37; CI ¼ 1.05-1.80) compared with random samples of healthy Danes aged 50-64 years.…”
Section: Discussionmentioning
confidence: 91%
“…It is expressed mainly by BM stromal cells, but is also expressed by myeloma cells and, to a lesser extent, by plasma cells in patients with monoclonal gammopathy of undetermined significance (MGUS). [18][19][20] IL-1b is important for both regulation of inflammation and of host defense in man, and it stimulates the production of IL-6, an important growth factor for MM cells. A recent study has shown that IL-1b-induced stimulation of IL-6 The polymorphism IL-1b T-31C and multiple myeloma AJ Vangsted et al production in BM stromal cells is higher in stromal cells from patients with myeloma than in stromal cells from patients with MGUS.…”
Section: Discussionmentioning
confidence: 99%
“…95,96 Myeloma stromal cells produce IL-6 in response to IL-1b. 97,98 This seminal observation has guided clinical research incorporating a recombinant form of the natural IL-1b antagonist, IL-1RA (anakinra), in the treatment of indolent myeloma. Anakinra controlled the proliferative fraction of myeloma cells and prolonged the chronic phase of the disease in several patients, thus providing clinical validation for the concept that blocking the actions of IL-1b is effective in halting progression of indolent myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the fact that PC from high-risk MM patients have been described to express high levels of IL-1β, this may seem surprising. IL-1 is thought to stimulate para-and autocrine IL-6 production in MM (15,16), and is a known physiological activator of NF-κB in B-lymphoid cells (17). Activation of NF-κB through FAK has been reported to play a role in IL-6 production in myoblasts (18).…”
Section: Phosphoproteome Of Normal Pcmentioning
confidence: 99%